2007
DOI: 10.1211/jpp.59.3.0007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of low levels of plasma valproic acid concentration following simultaneous administration of sodium valproate and rizatriptan benzoate

Abstract: Drug interaction between rizatriptan benzoate, an anti-migraine agent, and sodium valproate (VPA-Na), an anticonvulsant, was studied in rats. When rizatriptan benzoate was administered orally immediately after VPA-Na oral administration, the pharmacokinetic parameters, such as plasma valproic acid (VPA) and area under the plasma concentration-time curve up to 3 h (AUC(0-3)), were significantly decreased compared with those in the control group. However, when rizatriptan benzoate was administered intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…An unexpected change in valproic acid (VPA) concentration after VPA-Na administration might be caused by some co-administered drugs (9,16). In addition, we reported that salicylate (15) and rizatriptan benzoate (8) affected plasma VPA concentration in rats. Therefore, many clinical situations may need reliable therapeutic drug monitoring of VPA for the appropriate dose because of unpredictable drug-interactions.…”
mentioning
confidence: 98%
“…An unexpected change in valproic acid (VPA) concentration after VPA-Na administration might be caused by some co-administered drugs (9,16). In addition, we reported that salicylate (15) and rizatriptan benzoate (8) affected plasma VPA concentration in rats. Therefore, many clinical situations may need reliable therapeutic drug monitoring of VPA for the appropriate dose because of unpredictable drug-interactions.…”
mentioning
confidence: 98%